Natural gas in the Eastern Mediterranean region between the conflict of regional axes and the competition of international strategic (قضايا سياسية, 2025)
Natural gas discoveries in the Eastern Mediterranean have marked a significant historical turning point for the countries of the region, which are relatively poor in primary energy resources. Over the past two decades, the Eastern Mediterranean has witnessed massive natural gas discoveries, most notably the fields appearing in Egypt, Leviathan and Tamar in Israel, and Aphrodite in Cyprus. These discoveries have transformed the region into a center of geopolitical competition and conflict between regional powers over the demarcation of maritime borders and the distribution of gas revenues. This has made it a matter of global strategic interest, as international powers have played decisive roles in the region. The United States and Europe have supported the formation of regional blocs such as the East Mediterranean Gas Forum (EMGF), in an attempt to achieve stability and enhance cooperation among the countries of the region. This demonstrates that natural gas in the Eastern Mediterranean is not only a promising economic resource, but also a tool for reshaping balances and alliances in the region, making it a focus of conflict between regional hegemonic strategies, national security calculations, and the interests of major international powers.